2018
DOI: 10.1089/nat.2018.0727
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Trafficking and Endosomal Release of Oligonucleotides: What We Know and What We Don’t

Abstract: Understanding the cellular uptake and intracellular trafficking of oligonucleotides provides an important basic underpinning for the developing field of oligonucleotide-based therapeutics. Whether delivered as "free" oligonucleotides, as ligand-oligonucleotide conjugates, or in association with various nanocarriers, all forms of oligonucleotide enter cells by endocytosis and are initially ensconced within membrane-limited vesicles. Accordingly, the locus and extent of release to the cytosol and nucleus are key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 113 publications
3
92
0
Order By: Relevance
“…A biotin‐tagged ASO was co‐electroporated (2 % of 12.5 μ m ) with the unmodified ASO into human embryonic kidney (HEK 293T) cells and imaged with the aid of fluorescently labelled streptavidin (Figure A, B). The biotinylated ASO concentrates in granular structures inside the cell (for transfection rates see Section 1.9 in the Supporting Information), likely reflecting accumulation of the drug in the endocytic pathway or in cytoplasmic structures, as supported by the literature …”
Section: Figurementioning
confidence: 61%
“…A biotin‐tagged ASO was co‐electroporated (2 % of 12.5 μ m ) with the unmodified ASO into human embryonic kidney (HEK 293T) cells and imaged with the aid of fluorescently labelled streptavidin (Figure A, B). The biotinylated ASO concentrates in granular structures inside the cell (for transfection rates see Section 1.9 in the Supporting Information), likely reflecting accumulation of the drug in the endocytic pathway or in cytoplasmic structures, as supported by the literature …”
Section: Figurementioning
confidence: 61%
“…Besides, from the sorting endosomes, most amphiphilic molecules enter the endocytic recycling pathway . Lipid recycling at the plasma membrane is a highly dynamic and effective process, and antiproliferative APL produced in situ from the nucleic acid carrier is prone to trafficking at the plasma membrane where it can operate intrinsic apoptotic activity . Starting from erufosine, one of the most promising APLs to date, original lipid constructs were thus imagined for simultaneously implementing gene therapy and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This processt hus triggersa nd facilitates nucleic acid decondensation, which is requiredf or nucleic acid processing by the cell translation machinery.B esides, from the sorting endosomes, mosta mphiphilic molecules enter the endocytic recycling pathway. [18] Lipid recycling at the plasma membrane is ahighly dynamic and effective process, [19] and antiproliferative APL produced in situ from the nucleic acid carrier is pronet ot rafficking at the plasma membrane where it can operate intrinsic apoptotic activity. [20] Starting from erufosine,o ne of the most promising APLs to date, originall ipid constructs were thusi magined for simultaneously implementing gene therapy and chemotherapy.Aseries of 16 biolabile cationic lipids have been designed which can regenerate erufosine in situ under ac hemical or enzyme stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In either scenario, this is likely to be of benefit for intracellular delivery. Recent work has shown that the majority of endosomal escape occurs in late endosomes/ multivesicular bodies [107], suggesting that trapping at this stage of the pathway or increasing retention time before lysosomal degradation would be beneficial. In addition to avoiding lysosomal degradation, recycling is another limiting factor of nucleic acid delivery.…”
Section: (B) Mp Entry Favours Cargo Delivery To Late Endosomes and Mumentioning
confidence: 99%